The Effect of Acupressure on Increasing Breast Milk Production: A Scoping Review - Annisa, Pariqa; Mufdlilah, Mufdlilah (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Breast milk is the main source of nutrition for newborns under six months. During the first six months of life, babies receive full breast milk. This literature analysis aims to find the latest data from scientific research on the effect of acupressure in increasing breast milk production. The method used as a research design is Scoping Review. A scoping review is a precursor to a systematic review, which aims to identify the types of evidence available on the topic being discussed. They used the PRISMA-ScR framework by searching for articles through relevant databases. The research showed that acupressure effectively increased breast milk production, and acupressure at the SI 1, ST 18, ST 16, ST 17 and LU 1 acupressure points could affect breast milk production. This is because acupressure is a non-pharmacological technique that can increase breast milk production by pressing, rubbing and massaging various body parts to increase breast milk production and calm the body. Of the total 199 articles obtained, according to the inclusion criteria, there were ten relevant articles. Articles published between 2019 and 2023, articles available in Indonesian and English, articles that discuss improving acupressure to increase breast milk production, and articles available in full can all be accessed easily.